How moving together binds us together: The social consequences of interpersonal entrainment and group processes - Cross, L. *; Turgeon, M.; Atherton, G. * (De Gruyter, 2019)
Interpersonal entrainment has been shown to have a wide variety of social consequences which span far beyond those that could be considered purely pro-social. This work reviews all of the social effects of entrainment and the various explanations for them. The group formation framework emerges as a parsimonious account claiming that as we entrain our sense of self is temporarily diluted as an interdependent identity becomes more salient, thus leading to a range of social and psychological consequences which are pro-group. The sense of belonging arising from moving together is conducive towards pro-social behaviours; yet, it also makes the individual more susceptible to adopting the ideology of the group without critical thinking. We argue that the wide landscape of interpersonal entrainment’s effects reflects its primary effect, de-individuation, and the formation of a common group identity amongst co-actors.